Developing a Problem-Based Application to Enhance Students’ Digital Literacy in EFL Learning - Krisdiana, Amy; Mardiana, Wiwik; Anggraini, Andri Yulia (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2026)
The integration of mobile technology with Problem-Based Learning (PBL) offers a promising pathway to enhance students’ digital literacy in EFL contexts. This study developed and validated an Android-based English learning application grounded in PBL principles to support junior high school students’ digital literacy development. Employing a research and development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate), the product was evaluated through expert validation and field testing. Three expert validators assessed the application in terms of content, language, and media quality, while 81 ninth-grade students from two Indonesian public junior high schools (SMPN 2 Mojoanyar and SMPN 3 Mojokerto) participated in a four-week implementation. The application was designed around five PBL principles: authentic problem presentation, student-centered learning, collaboration, self-directed learning, and metacognitive reflection. Expert validation indicated strong quality in content (86%), language (91%), and media (76%). Students’ digital literacy scores increased from M = 28.47 (SD = 2.84) to M = 47.48 (SD = 1.52), t(80) = 58.84, p < .001. Indicator-level analysis showed the highest gains in self-regulated learning, interactive feature use, and digital communication. Practicality results indicated that students perceived the application as practical and supportive (overall 75.58%). While the pretest–posttest improvement suggests substantial learning gains, the one-group design warrants cautious interpretation. Overall, the findings support the feasibility of integrating PBL into mobile-assisted EFL learning to foster students’ digital literacy in alignment with the Merdeka Curriculum.